2007
DOI: 10.1364/ao.46.000620
|View full text |Cite
|
Sign up to set email alerts
|

Detection of vapors of explosives and explosive-related compounds by ultraviolet cavity ringdown spectroscopy

Abstract: The detection of vapors of dinitrobenzenes and dinitrotoluenes by UV cavity ringdown spectroscopy (CRDS) was investigated. Absorption cross sections at 248 nm were estimated by measurements on saturated vapors and compared with solution-phase values. The computed subparts per 10(9) detection sensitivity with no effort at preconcentration was demonstrated through measurements on diluted flows. The factors affecting measurements on 1 atm total pressure were considered, and it was demonstrated that Rayleigh scatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Therefore, fluctuations in laser intensity do not influence the accuracy of the measurement. For explosives, sub-ppb detection limits have been reported [70] using CRDS in the UV spectral range. Despite the high sensitivity they discuss the disadvantage of comparing poor selectivity in the UV range and possible interference with ozone, and propose the combination of their sensor with a second, less sensitive but more selective one [70].…”
Section: Cavity Ring Down Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, fluctuations in laser intensity do not influence the accuracy of the measurement. For explosives, sub-ppb detection limits have been reported [70] using CRDS in the UV spectral range. Despite the high sensitivity they discuss the disadvantage of comparing poor selectivity in the UV range and possible interference with ozone, and propose the combination of their sensor with a second, less sensitive but more selective one [70].…”
Section: Cavity Ring Down Spectroscopymentioning
confidence: 99%
“…For explosives, sub-ppb detection limits have been reported [70] using CRDS in the UV spectral range. Despite the high sensitivity they discuss the disadvantage of comparing poor selectivity in the UV range and possible interference with ozone, and propose the combination of their sensor with a second, less sensitive but more selective one [70]. Todd et al use CRDS in the MIR spectral region with an optical parametric oscillator as laser source and report ppb level detection for TNT, TATP, RDX, PETN, and Tetryl, and anticipate the possibility of detecting 75 ppt TNT with pre-concentration [35].…”
Section: Cavity Ring Down Spectroscopymentioning
confidence: 99%
“…They determined the LOD of TNT vapor by CRDS is less than 1 ppb. Ramos and Dagdigian recently presented a comprehensive study of the detection of vapors of DNBs and DNTs by UV CRDS (153). Their work showed that UV CRDS can detect ERCs at sub-ppb levels without any preconcentration.…”
Section: Uv/vis Absorptionmentioning
confidence: 99%
“…Various vapor sensors for explosive detection have been proposed and under intensive study, including electrochemical sensors 1-3 , surface acoustic wave (SAW) sensors [4][5][6] , quartz crystal mcrobalance sensors 7,8 , cantilever sensors 9, 10 , luminescencebased sensors [11][12][13] , spectroscopy [14][15][16] , and refractive index (IR) based optical sensors 17,18 . Some of these sensing techniques have achieved very high sensitivity towards common explosive ananlytes, for instance, 2, 4-dinitrotoluene (DNT) and 2, 4, 6-trinitrotoluene (TNT).…”
Section: Introductionmentioning
confidence: 99%